Landscape characteristics and honeybee colony integrity: A case study of Mwingi, eastern Kenya - Ochungo, Pamela Aor (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDConsEcol)--Stellenbosch University, 2020.